From International Horror Films to the Local Filem Seram: Examining the Cinematic Identity and Roles of the Malaysian Pontianak - Lee, Yuen Beng; Balaya, Sarata (Penerbit Universiti Sains Malaysia, 2016)
Malaysian horror films describe the pontianak as a supernatural entity with overflowing hair, vampire-like traits and a beautiful woman capable of seducing, charming and alluring her male victims. Once she has her target trapped, she transforms back into an unsightly pontianak and exacts her vengeance. Her capability of resurrecting from the afterlife and using her sexuality in seeking for death and destruction to those who have wronged her could position her as a villain or antagonist due to the chaos, destruction and murder to those regardless of innocence. Short of being labelled as a vamp or femme fatale, the pontianak continues being stereotyped as oppressive and monstrous for she gains supernatural strength and destablises a film's equilibrium. In short, the pontianak is seen as a threat towards partriachal order and such forms of representations are similarly shared in horror films globally. Using the films Sumpah Pontianak (1958) and Pontianak Harum Sundal Malam (2004), this paper examines the representation, identity and roles of the Malaysian cinematic pontianak within the contexts of local and global horror cinemas